Quo Vadis SMK Pusat Keunggulan? - Anggun Apriyani; Masduki Asbari; Mayada Latifatu Zakiyah; Iin Nuraeny (Journal of Information Systems and Management (JISMA), 2024)
The purpose of this study is to find out the vocational high school system through cooperation with various parties. Ministry of Education and Culture. In this study report, he uses a descriptive qualitative method by taking notes because the source of the data obtained by listening to the oral narration from the Youtube channel of the Indonesian Ministry of Education and Culture entitled "Merdeka Belajar Episode 8: Vocational High School Center of Excellence" which he presented. The program aims to develop vocational schools with certain expertise to become a reference and center for improving the quality and performance of other vocational schools. The development of vocational high schools that become centers of excellence is carried out holistically, including the involvement of industry, business, and the world of work in its development, the quality of student learning outcomes in vocational schools The episode contains the presentation of the minister of Education and Culture (Nadim Anwar Makarim) regarding the Merdeka Learning program. The program highlights the quality of Vocational High School facilities according to IDUKA standards of expertise competency needs and standards in other sectors, so that they become more qualified and competitive Centers of Excellence. Channeling government assistance to facilitate Vocational High Schools that are developed into centers of excellence, The program faces challenges, including the need for adequate funding, the need for qualified teachers, and the need for better coordination between learning assistance and curriculum assessment in vocational high school implementation programs.